2017
DOI: 10.3390/vetsci4020029
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of an Outbreak of Cryptosporidiosis among Veterinary Students

Abstract: An outbreak of gastrointestinal illness occurred among a cohort of 56 veterinary technology and 100 veterinary science students at Massey University over an eight-week period in 2013. This coincided with calving in New Zealand’s seasonal dairy farming system and a time when calves with diarrhoea are commonly seen by veterinarians. Laboratory and epidemiological investigations were instigated by MidCentral Public Health Service (MCPHS) in conjunction with the Institute of Veterinary, Animal and Biomedical Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Several students emphasized their interest in the exercise, but more than two thirds of the students declared nervousness about becoming sick in relation to the fetotomy exercise, and some students were observed wearing two face masks or four pairs of gloves on top of each other. This is in line with previous conceptions of enteric disease being a "rite of passage" in the veterinary curriculum, while nowadays the level of concern is higher (12). Several measures can be implemented to decrease the risk of cryptosporidiosis among veterinary students (12), including reducing the involvement of veterinary students with animals, which has however been suggested with a remark: "must be balanced with the value of clinical experience in producing practice-ready new graduates" (12).…”
Section: Downloaded Fromsupporting
confidence: 73%
See 1 more Smart Citation
“…Several students emphasized their interest in the exercise, but more than two thirds of the students declared nervousness about becoming sick in relation to the fetotomy exercise, and some students were observed wearing two face masks or four pairs of gloves on top of each other. This is in line with previous conceptions of enteric disease being a "rite of passage" in the veterinary curriculum, while nowadays the level of concern is higher (12). Several measures can be implemented to decrease the risk of cryptosporidiosis among veterinary students (12), including reducing the involvement of veterinary students with animals, which has however been suggested with a remark: "must be balanced with the value of clinical experience in producing practice-ready new graduates" (12).…”
Section: Downloaded Fromsupporting
confidence: 73%
“…Outbreaks of cryptosporidiosis in veterinary students have been widely reported and associated with direct handling of calves during academic training (12)(13)(14)(15)(16)(17). Some of these outbreaks have been linked to fetotomy exercises (14).…”
Section: Introductionmentioning
confidence: 99%
“…Because the transmission risk to humans depends on the species or genotype of the parasite, the molecular characteristics of the isolates is necessary for the assessment of epidemiological risk [3]. Using the molecular methods, Benschop et al [12] confirmed that 7 out of 156 veterinary science and veterinary technology students at Massey University in New Zealand were suffering from cryptosporidiosis. All 7 faecal specimens contained Cryptosporidium oocysts, whereas Cryptosporidium parvum IIa A18G3R1 was identified from one of the specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about the risk of giardiasis among veterinarians and other occupational groups exposed to animal carriers. According to NIZP-PZH data, every year in Poland about 1,300 cases of giardiasis are recorded in humans [12], with the risk of giardiasis among children reaching 12.5% [13]. The negative results of diagnostic tests for Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks have been described among caregivers and students of veterinary hospitals after contact with calves infected with C . parvum , the zoonotic species [ 86 ]. A major outbreak was reported in Milwaukee in 1993, in which 403,000 people were infected and the cost of outbreak-associated illness was US$96.2 million [ 87 , 88 ].…”
Section: Introductionmentioning
confidence: 99%